EXPLOITATION RESEARCH OF A CABLE SKIDDER TAF 690 PE FOR TIMBER SKIDDING IN THE WESTERN STARA PLANINA (Innovation in Woodworking Industry and Engineering design, 2026)
This paper presents the results of a study that was conducted to establish the basic perfor-mance characteristics of a specialized forestry tractor for skidding of a whole tree stems and long timber sections in mountainous conditions. The tractor travel speed at different gradients as well as the hourly productivity for a tree-length harvesting system in the Western Balkan Mountains region were determined. The regression analysis method was used to conduct the study and to determine the influence of various factors on the hourly productivity of the tractor, at a constant trip load volume. For this purpose, a planned two-factor experiment with three levels of variation of input factors was conducted. The time for tractor’s moving in different gradients was determined by timing. Running speeds were found at range from 3,23 to 4,82 km/h, hourly productivity from 5,36 to 10,98 m3/h with trip loads ranging from 6,9 to 8,5 m3. Regression equations were derived and by their use could be determined the productivity for different gradients and different lengths of skidding distances.